2019
DOI: 10.5334/tohm.463
|View full text |Cite
|
Sign up to set email alerts
|

Functional Movement Disorders in Elderly

Abstract: Background: Functional movement disorders (FMDs) have been rarely described in the elderly population. Methods: This is a retrospective chart review of elderly patients with FMDs (onset >60 years) attending the movement disorders clinic at a tertiary care teaching institute in India. Results: Out of 117 patients diagnosed with FMD at our center, 18 patients had an onset after the age of 60 years. The male-to-female ratio was 10:8 and the duration of symptoms ranged from 1 day to 5 years. Social (10/18) and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
3
11
0
Order By: Relevance
“…However, 10% of our patients were older than 60, which roughly matches the finding that 21% of patients with functional movement disorder have onsets after 60 years old [46][47][48][49]. Similar to FS, functional movement disorders are abnormal movements that may represent physical manifestations of psychological dysfunction [50].…”
Section: Kerr 15supporting
confidence: 84%
“…However, 10% of our patients were older than 60, which roughly matches the finding that 21% of patients with functional movement disorder have onsets after 60 years old [46][47][48][49]. Similar to FS, functional movement disorders are abnormal movements that may represent physical manifestations of psychological dysfunction [50].…”
Section: Kerr 15supporting
confidence: 84%
“…Functional tremor and gait disorders were the most commonly reported clinical manifestations in patients with elderly FMD onset. 5,8,9 Consistent with previous studies, tremor (47.1%) and gait disorders (29.4%) were also the most frequently reported symptoms in our cohort of patients with elderly FMD onset. A previous study indicated that functional gait phenotype was significantly more prevalent in individual with elderly FMD onset than in the younger population.…”
Section: Discussionsupporting
confidence: 92%
“…Younger adults are more commonly affected by FMD with a mean age at FMD onset ranging from 36.9 to 50 years old 4–6 . Few studies have dealt with FMD in the elderly pointing out that 10–21% of patients may have onset of their symptoms after the age of 60 5–9 . However, these studies may have not adequately addressed the presence of FMD in the elderly and how it differs from the younger age group with FMD.…”
mentioning
confidence: 99%
“…29 Another study reported that amongst 117 patients diagnosed with FMD at their center, 15% had an onset after the age of 60 years. 30 FNDs in children are common but differ from that in adults in terms of risk factors, phenomenology, and treatment response. 31 In general, FNDs are considered sporadic disorders but family history is described and may be an additional risk factor.…”
mentioning
confidence: 99%